The cyclooxygenase isozyme inhibitors parecoxib and paracetamol reduce central hyperalgesia in humans - Koppert, Wolfgang; Wehrfritz, Andreas; Körber, Nicole; Sittl, Reinhard; Albrecht, Sven; Schüttler, Jürgen; Schmelz, Martin (Pain (Amsterdam), 2004)
Non-steroidal antiinflammatory drugs (NSAIDs) are known to induce analgesia mainly via inhibition of cyclooxygenase (COX). Although the inhibition of COX in the periphery is commonly accepted as the primary mechanism, experimental and clinical data suggest a potential role for spinal COX-inhibition to produce antinociception and reduce hypersensitivity. We used an experimental model of electrically evoked pain and hyperalgesia in human skin to determine the time course of central analgesic and antihyperalgesic effects of intravenous parecoxib and paracetamol (acetaminophen). Fourteen subjects were enrolled in this randomized, double blind, and placebo controlled cross-over study. In three sessions, separated by 2-week wash-out periods, the subjects received intravenous infusions of 40 mg parecoxib, 1000 mg paracetamol, or placebo. The magnitude of pain and areas of pinprick-hyperalgesia and touch evoked allodynia were repeatedly assessed before, and for 150 min after the infusion. While pain ratings were not affected, parecoxib as well as paracetamol significantly reduced the areas of secondary hyperalgesia to pinprick and touch. In conclusion, our results provide clear experimental evidence for the existence of central antihyperalgesia induced by intravenous infusion of two COX inhibitors, parecoxib and paracetamol. Since the electrical current directly stimulated the axons, peripheral effects of the COX inhibitors on nociceptive nerve endings cannot account for the reduction of hyperalgesia. Thus, besides its well-known effects on inflamed peripheral tissues, inhibition of central COX provides an important mechanism of NSAID-mediated antihyperalgesia in humans.